2014
DOI: 10.5171/2014.141449
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Homocysteine Concentrations in Dogs

Abstract: Many human epidemiologic studies have reported associations between plasma homocysteine (Hcy) concentrations and cardiovascular disease, Alzheimer's disease, and osteoporosis. However, few studies have examined the relationship between Hcy and disease in dogs. In this study, we investigated the relationship between canine plasma Hcy concentrations and sex, age, breed, size; spay/neuter status, and disease. Plasma Hcy concentrations were related to sex and age, but the correlations were very weak. ShibaInu dogs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 21 publications
1
9
0
1
Order By: Relevance
“…Furthermore, potential sex-specific differences, the bioavailability of HCys and HCA in the brain and correlations between serum, urine and cerebral tissues were investigated. In similar previous experiments, hyperhomocysteinemia was mostly induced chemically and kinetic parameters were investigated within a maximum of 24 h [ 30 , 39 , 40 , 41 , 42 ]. In contrast, we conducted a long(er)-term kinetic study by inducing chronically elevated levels of HCys and HCA using a dietary approach and investigating both increases and decreases in these endogenous metabolites over 17 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, potential sex-specific differences, the bioavailability of HCys and HCA in the brain and correlations between serum, urine and cerebral tissues were investigated. In similar previous experiments, hyperhomocysteinemia was mostly induced chemically and kinetic parameters were investigated within a maximum of 24 h [ 30 , 39 , 40 , 41 , 42 ]. In contrast, we conducted a long(er)-term kinetic study by inducing chronically elevated levels of HCys and HCA using a dietary approach and investigating both increases and decreases in these endogenous metabolites over 17 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…The quantitative analysis of Hcy concentration was according to previous reported method. 21) Morris water maze test.…”
Section: Methodsmentioning
confidence: 99%
“…However, a higher prevalence of AD in offspring was observed in the offspring of women with elevated circulating levels of vitamins B 12 and folate, and hence upregulation of the homocysteine pathway may be related (109). Homocysteine is highly toxic for dogs (110), and blood homocysteine concentrations are kept low, lying within a narrow concentration range (111). Studies on mice have shown that homocysteine concentrations are kept low even in the case where serum concentrations of methionine (100), as well as cystathionine (106), are significantly increased.…”
Section: Diet Cohorts Readily Distinguished By Distinct Serum and Urimentioning
confidence: 99%